Amplop dan Barakah: Analisis Filantropi dan Patronasi dalam Tradisi Nyabis Kepada Kiai - Moh. Najibul Khair; Abdul Wahid (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
In Madurese culture, particularly within the community of Batuputih Laok Village, Batuputih, Sumenep, there exists a local tradition known as nyabis, performed by giving an “envelope” to a kiai. The increasing frequency and visibility of envelopes in the nyabis tradition among Batuputih Laok Village, Batuputih, Sumenep, community are not merely understood as acts of voluntarism or generosity, but are closely related to patronage relations and the pursuit of barakah (blessing). This study formulates research questions concerning how the meaning of the envelope is perceived, how patron–client relations are formed, and how barakah functions within the social structure of pesantren. The research employs a qualitative ethnographic approach through observation, interviews, and documentation. The findings indicate that the envelope is interpreted as an expression of philanthropy based on ta‘??m, tabarruk, and the strengthening of social bonds, while simultaneously serving as a medium of symbolic exchange between material resources and barakah. The results affirm that barakah functions as symbolic capital that reinforces the authority of the kiai and sustains intergenerational patronage relations.